Review paperThe interaction of coronary microembolization and ischemic preconditioning: A third window of cardioprotection through TNF-alpha - Heusch, Philipp; Skyschally, Andreas; Leineweber, Kirsten; Haude, Michael; Erbel, Raimund; Heusch, Gerd (Archives of Medical Science, 2007)
With an unstable atherosclerotic coronary plaque, episodes of myocardial ischemia associated with release of debris and microembolization and subsequent restoration of more or less sufficient coronary blood flow can precede ultimate plaque rupture, complete coronary occlusion and impending acute myocardial infarction. Such scenario involves both coronary microembolization with its established detrimental consequences for the dependent myocardium and repeated, transient episodes of myocardial ischemia/reperfusion which can induce protection by ischemic preconditioning. The current review aims to study the interaction between these adverse and beneficial effects. Experimental coronary microembolization in anesthetized pigs does not induce nor prevent acute preconditioning against infarction. However, six hours after coronary microembolization a third window of protection exists, which results from the upregulation of TNF-alpha. Apparently, TNF-alpha exerts bidirectional effects, i.e. induces contractile dysfunction but protects from infarction.